The pedicled thoraco-umbilical flap: A versatile technique for upper limb coverage - Sharad Mishra; Ramesh Kumar Sharma (Indian Journal of Plastic Surgery)
Injuries to upper limb has been on the increase and is invariably associated with significant soft tissue loss requiring a flap cover. Local tissue may not be available for cover in a majority of situations, necessitating import of tissue from a distant source. We have utilized the thoraco-umbilical flap taken from the trunk for this purpose. This flap is based on the perforators of the deep inferior epigastric artery that are maximally centred on the periumbilical region. This flap was used in 83 patients. The patients were observed for at least 3 weeks and any flap or donor site complications were recorded. The patients were again followed up at 3 months interval and the donor site scar was assessed. The flaps survived in 81 patients; there was marginal flap necrosis in five patients and partial flap necrosis in two patients. None of these patients required any additional procedure for coverage. The flap is technically easy to plan, almost effortless to drape around upper limb defects, with no significant donor site morbidity and also the post operative immobilization was fairly comfortable. The thoraco-umbilical flap thus is a very useful technique for coverage of the upper limb and is recommended as a first line flap for this purpose.